2012
DOI: 10.1002/eji.201242654
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin interactions are required for Langerhans cell differentiation

Abstract: Human skin contains the following two distinct DC subsets: (i) Langerhans cells (LCs), expressing Langerin but not DC-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN), are predominantly localized in the epidermis; and (ii) dermal DCs, expressing DC-SIGN but not Langerin, are observed mainly in the dermis. It is not known whether localization in the epidermis provides cues for LC differentiation. Here, we show that E-cadherin expressed by epidermal keratinocytes (KCs) is crucial for dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 23 publications
(33 reference statements)
6
30
1
Order By: Relevance
“…In the present study, we indeed demonstrated that E-cadherin expression was readily induced on MDLCs when cocultured with primary KCs and that this was partly due to the Notch signaling pathway activation as suggested by the DAPT blockade (28). Moreover, we provided further evidence that E-cadherin-dependent interactions between MDLCs and KCs were crucial to generate fully differentiated MDLCs as reported by others in two-dimensional cultures (45,58). Noticeably, to our knowledge, DLL1 does not exist as a clinical-grade reagent whereas GM-CSF, TGF-b1, and human albumin do, thus precluding the development of preclinical or clinical applications involving human LC-like cells using the DLL1 approach reported by Hoshino et al (28).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we indeed demonstrated that E-cadherin expression was readily induced on MDLCs when cocultured with primary KCs and that this was partly due to the Notch signaling pathway activation as suggested by the DAPT blockade (28). Moreover, we provided further evidence that E-cadherin-dependent interactions between MDLCs and KCs were crucial to generate fully differentiated MDLCs as reported by others in two-dimensional cultures (45,58). Noticeably, to our knowledge, DLL1 does not exist as a clinical-grade reagent whereas GM-CSF, TGF-b1, and human albumin do, thus precluding the development of preclinical or clinical applications involving human LC-like cells using the DLL1 approach reported by Hoshino et al (28).…”
Section: Discussionsupporting
confidence: 87%
“…These results demonstrated that the cell-to-cell contact between MDLCs and KCs was required to induce E-cadherin on MDLCs. Noticeably, these results were in total agreement with other recently published studies (45,46). A quantitative analysis of the E-cadherin induction on MDLCs in this setting confirmed the significant induction when MDLCs were cocultured with KCs (MFI of 207 6 57 versus 821 6 54) whereas supernatants led to a nonsignificant increase (MFI of 278 6 35; Fig.…”
Section: Cell-to-cell Contact With Kcs Is Critical To Induce E-cadhersupporting
confidence: 92%
“…We would predict that these will be especially important in relation to DC cross-talk with tissue structural cells, e.g. maturation signal provided by E-cadherin:E-cadherin between LC and KC (Mayumi et al, 2013).The dichotomy between molecular networks of human LCs and DDCs, recapitulating differences in their biology, may reflect a different origin of these cell types, as currently suggested by (Chorro and Geissmann, 2010;Hoeffel et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…GM-CSF and IL34, which bind to the same receptor, seem to play a critical role in LC differentiation and maintenance combination with TGFβ 302,313,317,318 . Finally, differentiation and maintenance of LCs in the epithelium requires adhesion between keratinocytes and LCs mediated by E-cadherin expressed on both cell types 319,320 .…”
Section: Immune Interactionsmentioning
confidence: 99%